Effects of Self-Staetments Coping Strategies - Uhlemann, Max R.; Plater, Sharon (Canadian Journal of Counselling and Psychotherapy, 2011)
There were three connected purposes of this study. One purpose was to examine the mediating role of self-statements in the stress-symptomatology relationship. The second was to assess the degree to which coping strategies discriminate between adaptive and maladaptive stress reactions. The third was to determine if a relationship exists between self-statements and coping strategies. Sixty-two female subjects completed the Life Experiences Survey, Hassles Scale, Hopkins Symptom (Checklist, and Physical Concerns Scale. In addition, journal entries of stressful incidents, self-talk patterns and coping strategies were obtained. Results = indicated that self-statements did not discriminate significantly between individuals who effectively or ineffectively handled stressful encounters. Only the information-seeking coping strategy showed a trend toward a significant effect on the stress-symptomatology relationship. Several categories of self-statements and coping strategies were significantly related. Implications of the findings are discussed.